A Challenge in Parenting: The Relation Between Parenting Stress and Regulation Emotion in Parent with Preschool Children - Nadhifah Nur Hafshah; Ari Pratiwi (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
The child development process cannot be separated from the role of parenting style to children. The demands in role as a parent is often trigger stress in parenting. These demands make parent needs to be able keep carry out their roles and dealing with the stress they feel. A person ability to cope with stress is related to emotional regulation This study aims to determine the relationship between emotion regulation and parenting stress in parents of preschool children. Method: This study uses a quantitative method with a correlational approach. This study involved 111 parents with 2 – 6 years old child and taking care their children directly based in Indonesia obtained by using purposive sampling technique. The scale used to measure emotional regulation is the Emotion Regulation Questionnaire (ERQ) and for using Parenting Stress Scale (PSS).